A Chinese Chan-based Mind-Body Intervention Improves Memory of Older Adults - Chan, Agnes S.; Cheung, Winnie K.; Yeung, Michael K.; Woo, Jean; Kwok, Timothy; Shum, David H. K.; Yu, Ruby; Cheung, Mei-chun (Frontiers in Aging Neuroscience, 2017)
There is growing interest in the adoption of lifestyle interventions to remediate age-related declines in memory functioning and physical and psychological health among older adults. This study aimed to investigate whether a Chinese Chan-based lifestyle intervention, the Dejian mind-body intervention (DMBI), leads to positive benefits for memory functioning in older adults. Fifty-six adults aged 60 years or older with subjective memory complaints (SMC) were randomly assigned to receive the DMBI or a control intervention (i.e., a conventional memory intervention; MI) once a week for 10 weeks; 48 of the adults completed the intervention. Participants’ verbal and visual memory functioning before and after the intervention were compared. In addition, changes in the participants’ subjective feelings about their memory performance and physical and psychological health after the intervention were examined. The results showed that both the DMBI and MI resulted in significant improvements in both verbal and visual memory functioning and that the extent of the improvements was correlated with participants’ level of performance at baseline. In addition, compared to the MI group, the DMBI group had significantly greater improvements in subjective physical and psychological health after the intervention. In summary, the present findings support the potential of the DMBI as an alternative lifestyle intervention for improving memory functioning, subjective physical and psychological health of older adults with SMC.